Accelerating Green Procurement for Construction Project Adoption Through The Enhancement of People Capabilities - Mohamad Bohari, Asmah Alia; Zafikha Aida Bidin,; Siti Nurul Ainun,; Natasha Khalil,; Norliana Sarpin,; Xia, Bo (International Journal of Sustainable Construction Engineering and Technology, 2024)
Unpredictable weather, global warming, and even air pollution result from human activities that harm the ecosystem, whether we like it or not. Since the publication of the Brundtland Report, the adverse effects on the environment have been the focus of discussion by many parties. The Brundtland report highlighted that the current physical development practices have less emphasis on environmental protection while planning physical growth. Since then, the construction sector has gradually embraced many green practices, such as green procurement. The people capability requirements that are crucial for speeding the adoption of green-oriented procurement will, therefore, be highlighted in this paper. This study uses an exploratory technique to uncover the people's capability criteria for green procurement of a construction project. The identification of the criteria is novel Several focus group discussion sessions were conducted involving stakeholders from various backgrounds who have been involved with green buildings. The results of this study will help the project stakeholders to enhance people capability plans for the project development. The ultimate aim is to ensure all the green project objectives are carried out in line with the urgent need to protect the environment and support government policies.